Intravenous line establishment and anesthesia induction in an upper extremity with congenital arteriovenous malformation - Ozer, Ayse Belin; Deniz, Ahmet; Karatepe, Umit; Altun, Serdar (Elsevier Science Inc, 2016)
[Abstract Not Available]